2016
DOI: 10.1111/jgs.14535
|View full text |Cite
|
Sign up to set email alerts
|

Preparing Family Caregivers to Recognize Delirium Symptoms in Older Adults After Elective Hip or Knee Arthroplasty

Abstract: Delivery of a telephone-based intervention appears feasible. All family caregivers who began the program completed the four education modules. Future studies evaluating the effectiveness of the educational program should include a control group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 26 publications
(69 reference statements)
0
33
0
Order By: Relevance
“…In contrast, both the Steis and Martins teams offered intensive training for family caregivers that would not be practical in an ED setting . In the study by Bull et al, family caregivers were trained in the 3 weeks before their family memberʼs elective surgery, to increase their knowledge of delirium and the use of the FAM‐CAM . Another important distinction between our study and the previous validations of the FAM‐CAM was our double blinding of ratings of caregivers and research staff.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In contrast, both the Steis and Martins teams offered intensive training for family caregivers that would not be practical in an ED setting . In the study by Bull et al, family caregivers were trained in the 3 weeks before their family memberʼs elective surgery, to increase their knowledge of delirium and the use of the FAM‐CAM . Another important distinction between our study and the previous validations of the FAM‐CAM was our double blinding of ratings of caregivers and research staff.…”
Section: Discussionmentioning
confidence: 95%
“…Similarly, among hospitalized older patients, Martins et al used the Portuguese version of the FAM‐CAM and observed high sensitivity (91%; 95% CI = 74%‐97%) and specificity (91%; 95% CI = 74%‐97%) against the CAM and against the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition, Text Revision , criteria (sensitivity = 75% [95% CI = 35%‐95%]; specificity = 86% [95% CI = 42%‐99%]) . Finally, in a study conducted by Bull et al among post–knee or hip surgery patients, a κ of 0.47 was observed between the FAM‐CAM and the CAM . The current study differs from these previous studies in several ways, in particular with regards to the training of family caregivers who completed the FAM‐CAM and the blinding of assessors.…”
Section: Discussionmentioning
confidence: 99%
“…The few researchers that have investigated the integration of family caregivers in care have underscored or evidenced that family caregivers can play a major role in preventing delirium (Bull et al, ; Martins, Conceição, Paiva, Simões, & Fernandes, ; Mitchell et al, ; Rosenbloom & Fick, ; Steis et al, ), particularly by handling certain aspects of care (e.g., comfort, orientation, reassurance). This collaboration has been found to be beneficial to family caregivers, who have reported a higher level of perceived support and respect from nurses (Al‐Mutair, Plummer, O'brien, & Clerehan, ; Mitchell, Chaboyer, Burmeister, & Foster, ).…”
Section: Discussionmentioning
confidence: 99%
“…The few researchers that have investigated the integration of family caregivers in care have underscored or evidenced that family caregivers can play a major role in preventing delirium (Bull et al, 2017;Martins, Conceição, Paiva, Simões, & Fernandes, 2014;Mitchell et al, 2017;Rosenbloom & Fick, 2014;Steis et al, 2012), particularly by handling certain aspects of care (e.g., comfort, ori-…”
Section: Implications For Practicementioning
confidence: 99%
See 1 more Smart Citation